2011
DOI: 10.3178/hrl.5.47
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient flux from Shiretoko into the ocean using MRI-GCM

Abstract: Abstract:This study aims to evaluate nutrient flux to the coast from the inland areas of Shiretoko in order to understand the key factors controlling the ecological systems of the coast. As an external force, rainfall is considered one of the most significant components controlling nutrient supply to coastal systems in this area. Therefore, to estimate nutrient supply in the future, the bias correction was applied by using Meteorological Research Institute Global Climate Model, which shows good agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…For example, Wilby and Harris () and Nakayama et al . () applied bias correction for precipitation, and projection of river discharge has been undertaken using normal distributions and cumulative distribution functions (cdf). Although wind speed is likely to increase in the future due to the increased occurrence of tropical cyclones (IPCC, ), there have been few studies on bias‐corrected wind relative to the large number of studies on precipitation and air temperature and their application to water quality.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Wilby and Harris () and Nakayama et al . () applied bias correction for precipitation, and projection of river discharge has been undertaken using normal distributions and cumulative distribution functions (cdf). Although wind speed is likely to increase in the future due to the increased occurrence of tropical cyclones (IPCC, ), there have been few studies on bias‐corrected wind relative to the large number of studies on precipitation and air temperature and their application to water quality.…”
Section: Introductionmentioning
confidence: 98%
“…Bias correction can easily be applied under different climatological conditions if meteorological data sets are available, and there have been many studies related to bias correction for precipitation and air temperature. For example, Wilby and Harris (2006) and Nakayama et al (2011) applied bias correction for precipitation, and projection of river discharge has been undertaken using normal distribu- Although wind speed is likely to increase in the future due to the increased occurrence of tropical cyclones (IPCC, 2012), there have been few studies on biascorrected wind relative to the large number of studies on precipitation and air temperature and their application to water quality. This study thus aimed to project the occurrence of strong negative winds over Tokyo Bay using 11 different models, MRI-AGCM3.1S, 3.1H, 3.1L and eight CMIP3 models, in order to investigate the possible recovery from hypoxia of Tokyo Bay in the future (2081 to 2099) relative to the present day (1980 to 1998) by assuming that other meteorological and hydrological conditions remain constant.…”
Section: Introductionmentioning
confidence: 99%
“…When we consider nutrient flux in a river flowing from the upstream end into the ocean, the flux depends on nutrients supplied not only inside the river itself but also from the entire river basin (Dutta and Nakayama, 2010;Alam and Dutta, 2012;Riggsbee et al, 2008). Also, particulate nutrient flux, which is given from surface soils dominantly, is revealed to be larger than dissolved nutrient generally in a mountainous region (Nakayama et al, 2011). Cederholm et al (1989) demonstrated that mammals and birds consume migrating fish, which may result in the secondary dispersion of MDN across the river basin associated with the movement of these consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the six stations were chosen from three different regions, the Atlantic Ocean side (GAT and LMB), the inland (ALA and GAM) and the Pacific Ocean side (PMG and BHT), respectively, in order to understand the long-term trend of precipitation in the different climate regions. (11) where, Rx1day is the annual maximum 1 day precipitation, Rx5day is the annual maximum consecutive 5 day precipitation, SDII is the simple precipitation intensity index, R10mm is the annual I_164 Table 1 Climate change indices at six meteorological stations. nc means no clear trend by using Mann-Kendall trend test.…”
Section: Climate Change Indices (1) Long-term Precipitation Data In Pmentioning
confidence: 99%